Tonically Active α(5)GABA(A) Receptors Reduce Motoneuron Excitability and Decrease the Monosynaptic Reflex - Canto-Bustos, Martha (Front Cell Neurosci, 2017)
Motoneurons, the final common path of the Central Nervous System (CNS), are under a complex control of its excitability in order to precisely translate the interneuronal pattern of activity into skeletal muscle contraction and relaxation. To fulfill this relevant function, motoneurons are provided with a vast repertoire of receptors and channels, including the extrasynaptic GABA(A) receptors which have been poorly investigated. Here, we confirmed that extrasynaptic α5 subunit-containing GABA(A) receptors localize with choline acetyltransferase (ChAT) positive cells, suggesting that these receptors are expressed in turtle motoneurons as previously reported in rodents. In these cells, α(5)GABA(A) receptors are activated by ambient GABA, producing a tonic shunt that reduces motoneurons’ membrane resistance and affects their action potential firing properties. In addition, α(5)GABA(A) receptors shunted the synaptic excitatory inputs depressing the monosynaptic reflex (MSR) induced by activation of primary afferents. Therefore, our results suggest that α(5)GABA(A) receptors may play a relevant physiological role in motor control.